Genetic Divergence in Stem Amaranth (Amaranthus tricolor L.) Genotypes for Yield and its Component Characters (The Agriculturists, 2013)
An investigation was carried out to identify the extent of genetic divergence that exist for the yield and yield contributing characters of seventeen genotypes of amaranth using Mahalanobis D2 analysis. Analysis of variance showed significant difference among the genotypes for most of the characters studied. The genotypes under study fell into 4 clusters. The distribution pattern indicated that the maximum number of genotypes (6) was included in cluster (IV) followed by cluster III (5) and cluster II (5), and the minimum number was in cluster I (1). The inter cluster distance in most of the cases was higher than the intra cluster distance, which indicated wider genetic diversity among the accessions of different groups. The highest inter cluster distance was observed between IV and I, followed by the distance between cluster II and I showing wide diversity among the groups. The lowest inter-cluster distance was observed between clusters III and II suggesting a close relationship among the genotypes of these two clusters. The highest intra-cluster distance was observed for the cluster IV and the lowest for the cluster I. The positive values of vector I and vector 2 for stem weight and weight of leaf indicated that these two characters had the highest contribution towards the divergence among the stem amaranths. The genotypes of stem amaranth from cluster I and cluster IV may be selected as parents in future hybridization program. DOI: http://dx.doi.org/10.3329/agric.v11i1.15247 The Agriculturists 2013; 11(1) 82-88